The section Secretary of the historical files of seminars, a reference point for studies of history of education: the example of the Metropolitan Seminary San Aton of Badajoz - Vivas Moreno, Agustín; Pérez Ortiz, Guadalupe; González Lozano, Francisco (Revista General de Información y Documentación, 2017)
The Metropolitan Seminar San Aton Badajoz, as a training centre of reference in Extremadura, has generated throughout its history a wide-ranging documentary heritage in the field of education and pedagogy. Proof of this is found in the wealth of their file. The researchers to ensure in education and in teaching methods between the seventeenth to the twentieth century necessarily your look at this interesting file. Within the classification table of the same we must make a special mention to the documentary series Secretariat because this is where we find the content more meaningful for the study of the entity, as well as students who have studied in it, of the educational methods and pedagogical, etc.